Effective pressure sensor using the parity-time symmetric photonic crystal. (27th February 2023) - Zaky, Zaky A; Al-Dossari, M; Sharma, Arvind; Aly, Arafa H
Abstract: Monitoring the variations in pressure, distribution, and the magnitude of the emitted gases at the ground surface is very important in different applications. Because of the parity-time symmetric mechanism, a novel one-dimensional photonic crystal as a pressure sensor is proposed. The transmittance spectra are calculated and analyzed using the transfer matrix method. The parity-time symmetric property amplifies the transmittance of the defect mode and gives an additional hand to enhance the magnification and performance of the sensor. The optimum conditions are the normal angle of incidence, defect layer thickness of 1400 nm, the porosity of the porous silicon layer of 80%, and macroscopic Lorentz oscillation intensity of 5 × 10 -4 . The results show that the position and amplitude sensitivities are 4.9 nm GPa −1 and 1844%/GPa. That means in such sensors, by altering pressure, the desired value of magnified transmittance and sensitivity can be achieved as required according to the optical communication devices. Therefore, the proposed device performs better with high precision and accuracy. Consequently, it is much more helpful in optical communication and optoelectronic devices.